2010
DOI: 10.1093/humupd/dmq015
|View full text |Cite
|
Sign up to set email alerts
|

Predictive factors in in vitro fertilization (IVF): a systematic review and meta-analysis

Abstract: Female age, duration of subfertility, bFSH and number of oocytes, all reflecting ovarian function, are predictors of pregnancy after IVF. Better quality studies are necessary, especially studies that focus on embryo factors that are predictive of success in IVF.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

19
217
4
6

Year Published

2011
2011
2017
2017

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 279 publications
(246 citation statements)
references
References 71 publications
19
217
4
6
Order By: Relevance
“…This view is further supported by a recent meta-analysis that found that female age is the most important predictor of pregnancy in IVF in almost all the analyzed studies [27].…”
Section: Discussionmentioning
confidence: 55%
“…This view is further supported by a recent meta-analysis that found that female age is the most important predictor of pregnancy in IVF in almost all the analyzed studies [27].…”
Section: Discussionmentioning
confidence: 55%
“…Although the most desirable endpoint for transcriptomics studies is live birth, several studies examined the gene expression of CC in relation to embryo development (McKenzie et al 2004, Hasegawa et al 2005, Zhang et al 2005, Cillo et al 2007, Feuerstein et al 2007, Anderson et al 2009, Assou et al 2013. As embryos with the best morphological appearance are usually selected for uterine transfer and have been shown to implant at a higher rate than morphologically low-quality embryos (van Loendersloot et al 2010), the gene expression profiles of these studies may serve as an indirect marker of embryo viability and be at least loosely related to live birth rates.…”
Section: Microarray and Qrt-pcr Studies In Ivf Populations In Relatiomentioning
confidence: 99%
“…ARTs, and in particular in vitro fertilisation (IVF), have become a widely accepted form of reproduction since they emerged in the late 1970s [23]. It is estimated that over 5 million children have now been born worldwide as a result of ART treatments.…”
Section: Medical Virtue and Commerce In The 21 St Century: The Case Omentioning
confidence: 99%